Teachers' Understanding of the Game-Based Learning Model in South and West Sulawesi: Rasch's Analysis - Riskawati; Khaeruddin; Nirwana; Tisa Rifsa; Adinda Futri Syasbila; Nurhikma Syam; Hendra B; Sitti Rahma Yunus (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
Game-based learning is an approach that applies elements of play to enhance student engagement, motivation, and conceptual understanding in interactive ways. This study analyzes teachers’ understanding of the model and evaluates the psychometric quality of the instrument used. A quantitative descriptive method with Rasch analysis was employed to test validity, reliability, and fairness. The sample consisted of 54 chemistry teachers in South and West Sulawesi, selected randomly from diverse demographic backgrounds. Data were collected using questionnaires designed to measure teachers’ comprehension of the concept and application of game-based learning. Results indicated that the instrument demonstrated strong psychometric properties, with high validity and reliability, and appropriate item difficulty relative to teachers’ abilities. No significant differences were observed across gender, age, or teaching level, confirming the fairness of the instrument. However, teachers aged 25–34 and those at the elementary level displayed higher understanding. These findings highlight the need for targeted training to support teachers with lower comprehension, thereby promoting optimal implementation of game-based learning across educational levels.